Optimization of the collecting mirror location in the plasma source of extreme ultraviolet radiation - Borgun, Ie.V.; Hrechko, Ya.O.; Azarenkov, N.A.; Dimitrova, V.D.; Ryabchikov, D.L.; Sereda, I.N.; Hryhorenko, A.V.; Tseluyko, A.F. (Вопросы атомной науки и техники, 2015)
The paper is devoted to searching the optimal location of first collecting mirror in the extreme ultraviolet radiation plasma sources. It is shown that the system efficiency can be increased by 1.5…2.5 times in the case of elliptical plasma radiation pattern and the optimal location of the first collecting mirror. In this case the first collecting mirror should cover the plasma on lateral side. Работа посвящена поиску оптимального расположения первого собирающего зеркала в плазменных источниках экстремально ультрафиолетового излучения. Показано, что в случае эллиптической диаграммы направленности излучения плазмы и оптимального расположения первого собирающего зеркала можно в 1,5…2,5 раза повысить эффективность системы. В этом случае первое собирающее зеркало должно охватывать боковую поверхность плазмы. Роботу присвячено пошуку оптимального розташування першого збираючого дзеркала в плазмових джерелах екстремально ультрафіолетового випромінювання. Показано, що в разі еліптичної діаграми спрямованості випромінювання плазми та оптимального розташування першого збирального дзеркала можна в 1,5…2,5 рази підвищити ефективність системи. У цьому випадку перше збиральне дзеркало має охоплювати бокову поверхню плазми.